Factor VII Activation, Apolipoprotein A-I and Reverse Cholesterol Transport: Possible Relevance for Postprandial Lipaemia - Miller, G. J.; Cooke, C. J.; Nanjee, M. N.; Howarth, D. J.; Cooper, J. A.; Stepanova, I. P.; Morrissey, J. H.; Miller, N. E. (Thrombosis and Haemostasis, 2002)
Postprandial lipaemia is associated with activation of factor VII (FVII) and efflux of cholesterol from tissues to nascent plasma high density lipoproteins (HDL) containing apolipoprotein A-I (apo A-I). To determine whether FVII activation and cholesterol efflux occur together in other situations, the responses to intravenous infusion of HDL-like apo A-I/phosphatidylcholine discs were measured in 10 healthy men. Disc infusion (40 mg apo A-I/kg body weight) over 4 h was followed by increases in HDL cholesteryl ester and plasma apo A-I (p <0.0001). Significant activation of FVII was apparent during infusion in fasting subjects (p = 0.03), activated FVII averaging 123% of baseline value by 12 h (p <0.0001). Plasma thrombin-antithrombin (TAT) complex increased to 156% of baseline level by 12 h (p >0.05) but individual responses differed considerably. Peak TAT post-infusion was associated inversely with peak HDL triglyceride concentration (p = 0.004). The coagulation responses to disc-infusion may be due to transfer of phosphatidylserine to cell surfaces during cholesterol efflux.
Keywords: Factor VII; apolipoprotein A-I; high density lipoprotein; phospholipids; reverse cholesterol transport